Pulmonary alveolar microlithiasis combined with gastric mucosal calcification: a case report - Li, Wen-Zhuo; Liu, Shuo; Luo, Ji-Li; Xia, Jing (Frontiers in Medicine, 2024)
Background: Pulmonary alveolar microlithiasis is a rare disease whose clinical and imaging manifestations are non-specific, characterized by the deposition of microliths in the alveoli that mostly consist of calcium and phosphorus. Combined calcification of other organs is even less common.Case Presentation: A 59-year-old woman was admitted to our hospital due to a cough with white foam sputum, dyspnea, and fever for 20 days. The CT scan showed diffuse ground-glass opacities and calcification of the gastric mucosa. Lung tissue biopsy revealed calcification and foreign body granulomatous in the interstitium and alveolar cavity. In the later stages, she developed painful skin petechiae. For this patient, the diagnosis of pulmonary alveolar microlithiasis, gastric mucosal calcification, and purpura fulminans was made. However, the genetic test results hinted that the patient and her son had a heterozygous mutation in the FBN1 gene, but her daughter's genetic test result was normal. Although the patient received anti-infection treatment, steroids, and oxygen therapy, her condition did not improve.We reported a rare case of PAM combined with calcification of other organs and purpura fulminans. Treatment of steroids did not show any benefit. The causative mechanism and effective treatment of this disease remain unclear. More treatments need to be explored.